Характеристика повноважень територіальних управлінь Державного бюро розслідувань - Богданов, Р. І.; Bohdanov, R. I. (Вісник Харківського національного університету внутрішніх справ. – 2024. – № 2 (105), ч. 1. - С. 84-92, 2024)
Проаналізовано наукові погляди вчених щодо розуміння поняття «повноваження територіальних управлінь Державного бюро розслідувань». Спираючись на проведений аналіз, зроблено висновок, що повноваженнями є законодавчо встановлений обсяг прав та обов’язків, який дозволяє повною мірою та максимально ефективно реалізувати завдання і функції територіальних управлінь Державного бюро розслідувань. Зазначено, що відповідні повноваження найбільш доцільно поділити на дві групи: 1) за суб’єктом, якому повноваження належать; 2) за спрямованістю.

The article focuses on the fact that the creation of the State Bureau of Investigation of Ukraine was an important step towards ensuring the high-quality and efficient functioning of the entire law enforcement sector of our country, as well as the establishment of the rule of law and legality. It is argued that in the current context, the State Bureau of Investigation is beginning to play an increasingly important role in ensuring the proper functioning of all other state institutions. It is emphasised that the work of the State Bureau of Investigation directly depends on the quality and effectiveness of the powers of its territorial offices. Based on the analysis of scientific views of scholars, it is noted that powers are a legally established scope of the rights and obligations which allows to implement the tasks and functions of the territorial offices of the State Bureau of Investigation to the fullest extent and with maximum efficiency. It is stated that these powers are exercised both by the central office of the State Bureau of Investigation and by the territorial departments; the factor determining the scope of application of the powers is the competence of these entities, including the territories covered by their activities. It is determined that the powers are aimed at protecting the legitimate interests of SBI employees in a fair assessment of their service, career and professional growth, and the absence of obstacles to their professional activities. It is argued that the powers of the territorial offices of the State Bureau of Investigation should be divided into two large groups: a) according to the subject to whom the powers belong such as: the head, investigators, employees of operational units, employees of auxiliary units (e.g., personnel, financial and economic); b) according to the orientation 1) on the direct implementation of the SBI’s tasks (rule-making, personnel and organisational, information and analytical, pre-trial investigation and operational search activities, methodological, protection of public property interests, in the field of cooperation); 2) related to the organisation of effective performance of the above powers (careful treatment of property, ethical behaviour, etc.)

Проанализированы научные взгляды ученых относительно понимания понятия "полномочия территориальных управлений Государственного бюро расследований". Опираясь на проведенный анализ, сделан вывод, что полномочиями является законодательно установленный объем прав и обязанностей, позволяющий в полной мере и максимально эффективно реализовать задачи и функции территориальных управлений Государственного бюро расследований. Отмечено, что соответствующие полномочия целесообразно разделить на две группы: 1) по субъекту, которому полномочия принадлежат; 2) по направленности.
Characteristics of the State Bureau of Investigation’s territorial departments’ powers
Keywords: повноваження; правовий статус; територіальні управління; Державне бюро розслідувань; powers; legal status; territorial departments; State Bureau of Investigation; полномочия; правовой статус; территориальные управления; Государственное бюро расследований